2019
DOI: 10.3389/fonc.2018.00652
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Utilization Pattern of Liquid Biopsies (LB) to Detect Actionable Driver Mutations, Guide Treatment Decisions and Monitor Disease Burden During Treatment of 33 Metastatic Colorectal Cancer (mCRC) Patients (pts) at a Fox Chase Cancer Center GI Oncology Subspecialty Clinic

Abstract: Background: Liquid biopsy (LB) captures dynamic genomic alterations (alts) across metastatic colorectal cancer (mCRC) therapy and may complement tissue biopsy (TB). We sought to describe the utility of LB and better understand mCRC biology during therapy.Methods: Thirty-three patients (pts) with mCRC underwent LB. We used permutation-based t-tests to assess associations between alts, and clinical variables and used Kendall's tau to measure correlations.Results: Of 33 pts, 15 were women; 22 had colon, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…During anti‐cancer drug treatment, subclones survive and multiply, contributing to further evolution of metastases into diverse tumor cell phenotypes. Several studies demonstrated that at disease progression, expanding clones are different with respect to those identified at the beginning in tumor biopsy and that expanding clones may be selected by progresses therapies and have differential sensitivities to therapy . This was extensively shown for both hematological and solid tumors …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During anti‐cancer drug treatment, subclones survive and multiply, contributing to further evolution of metastases into diverse tumor cell phenotypes. Several studies demonstrated that at disease progression, expanding clones are different with respect to those identified at the beginning in tumor biopsy and that expanding clones may be selected by progresses therapies and have differential sensitivities to therapy . This was extensively shown for both hematological and solid tumors …”
Section: Introductionmentioning
confidence: 99%
“…2 This was extensively shown for both hematological [3][4][5] and solid tumors. 1 Large-scale studies demonstrated a limited usefulness of molecular profiling obtained from Formalin-Fixed and Paraffin-Embedded tumor specimen of primary tumor, relapse, or metastasis. 6 Tumor biopsies normally accomplish the sampling of only a part of the tumor and may only capture a fraction of its heterogeneity, consequently not being totally informative about the levels of genetic variability of a patient's cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 European Institute of Oncology, Milan, Italy. 4 Oncology, Azienda Ospedaliera Universitaria Senese, Siena, Italy.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Classically, haematological malignancies have taught us that, within the dynamic clonal evolution, a subclonal expansion of a pre-existing mutated clone leads often to relapse [2,3]. Expanding clones may be selected by treatment acquiring drug resistance and patients who relapse after an effective therapy usually have a poor prognosis [4,5]. While at the beginning of tumor expansion there is a consistent, although variable, mutational burden from ten to hundred clones, at relapse the leading clone is usually only one [5].…”
Section: Introductionmentioning
confidence: 99%